Distributed resilient secondary control strategy for DC microgrids under cyber-attacks - Jiang, Xuan (Nanyang Technological University, 2023)
DC microgrid has attracted a lot of attention in recent years due to its ability to integrate various renewable energy sources. However, since DC microgrids usually rely on communication between each distributed generator (DGs) in implementation, it is vulnerable to cyber-attacks, such as DoS and FDI. In this dissertation, a distributed resilient control algorithm that enables DC microgrids to cope with both DoS and FDI attacks is put forward. Initially, the advantages of multiple-bus DC microgrids are compared with AC microgrids, and single-bus microgrids are analyzed. Next, the hierarchical control architectures of microgrids are discussed. After this, a physical model of islanded DC microgrids in the case of no attack is constructed. Subsequently, a DoS attack model is constructed with assumptions about attack duration and frequency. A distributed resilient control algorithm, which can be applied to each distributed generator separately, is designed to resist DoS attacks on the communication links between DGs. Then FDI attacks are modeled with the amplitude-bounded unknown function caused by the attacks. To compensate for the effects of FDI on DC MGs, an intermediate observer is included in the distributed controller. Afterward, the second method of Lyapunov is used to prove that the DC MGs under DoS and FDI attacks with the proposed control method can realize power sharing and global voltage restoration. Then appropriate controller parameters are selected through rigorous theoretical analysis. Finally, case studies based on Simulink show that the control strategy can make DC MGs resist DoS attacks and FDI attacks simultaneously.